A multicenter report on the safety and efficacy of plerixafor based stem cell mobilization in children with malignant disorders. Issue 3 (21st January 2021) - Bhunia, Nabanita; Abu‐Arja, Rolla; Stanek, Joseph R.; Mehyar, Lubna S.; Shaw, Peter J.; Kang, Hyoung Jin; Stein, Jerry; O'Brien, Tracey A.; Roberts, Catherine H.; Lee, Anselm Chi‐wai; Loeb, David M.; Ozkaynak, Mehmet F.; et al.
Abstract: Background: Pleraxifor for peripheral blood stem cell (PBSC) mobilization in children with malignancies is often given following failure of standard mobilization (SM) rather than as a primary mobilizing agent. Study Design and Methods: In this retrospective multicenter study, we report the safety of plerixafor‐based PBSC mobilization in children with malignancies and compare outcomes between patients who received plerixafor upfront with SM (Group A) with those who received plerixafor following failure of SM (Group B). In the latter pleraxifor was given either following a low peripheral blood (PB) CD34 (<20 cells/cu.mm) (Group B1) or as a second collection process due to an unsuccessful yield (CD34 + < 2 × 10 6 /kg) (Group B2) following failed SM and first apheresis attempts. Results: The study cohort (n = 47) with a median age of 8 (range 0.6‐21) year, comprised 19 (40%) Group A and 28 (60%) Group B patients (B1 = 12 and B2 = 16). Pleraxifor mobilization was successful in 87.2% of patients, similar between Groups A and B (84.2% vs 89.2%) and resulted in a median 4‐fold increase in PB CD34. Median number of apheresis attempts was 2 in Groups A and B1 but 4 in Group B2. In Group B2, median total CD34+ yield post‐plerixafor was 9‐fold higher than after SM ( P = .0013). Mild to moderate transient adverse events affected 8.5% of patients. Among patients who proceeded to autologous transplant (n = 39), all but one engrafted. Conclusion: Plerixafor‐based PBSC collection was safe and effective in our cohort and supports consideration as a primary mobilizing agent in children with malignancies.